Ritual learning method for mystical ijazah at pondok pesantren salafiyah - Ayubi, Sholahuddin Al; Masruri, Muhammad (Intelektual Pustaka Media Utama, 2025)
This study aims to explore mystical ritual learning methods to obtain mystical ijazah in Pesantren Salafiyah (Islamic Boarding Schools). The certificate of mysticism is a gift from the Kiai to the students. The Pesantren Salafiyah, known for its traditional approach to Islamic education, offers this unique learning experience to its students. This study examines the ritualistic aspects of obtaining a mystical diploma in the Salafi Islamic Boarding School. This study investigates the methods, practices, and teachings used by the Kiai and ustad to facilitate the spiritual growth and development of the students. Through qualitative research methods such as participant observation, interviews, and document analysis, this research explores traditions, ceremonies, and rituals integral to the learning process. The results revealed the importance of habits in enhancing the spiritual experience of students and building a solid connection with mystical teachings. Rituals include various elements, including reading sacred texts, meditation, physical exercise, and symbolic movements. In addition, the research findings explore the implications of ritual learning methods for mystical diplomas in Salafi Islamic Boarding Schools. It highlights a unique pedagogical approach by combining traditional Islamic education with esoteric teachings, encouraging a holistic understanding of spirituality. The study also discusses the challenges and opportunities contemporary Islamic educational institutions face in preserving and adapting ritual learning methods in a modern context